Tác động của chuyển đổi cơ cấu tuổi dân số đến tăng trưởng GDP bình quân đầu người ở Việt Nam - Phạm Thị Lý, Lý; Nguyễn Thanh , Trọng; Nguyễn Thị , Đông (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
Population age structure shapes the development trajectory and brings many opportunities and challenges for many countries. Population aging is a concern of both developed and developing countries, including Vietnam. From the growth accounting approach and neoclassical growth model, the authors design a regression function to estimate the relationship between population age structure and GDP per capita growth. In addition to economic factors such as savings rate and trade openness positively affecting economic growth, the results show that the proportion of working age and the young dependency rate also positively impact economic growth. Conversely, the old dependency ratio, the proportion of young workers, and human capital are still a burden on GDP per capita growth in Vietnam in the period 1991–2020.
Keywords: Population age structure; Economic growth; Vietnam